2010
DOI: 10.1007/s00330-010-1826-3
|View full text |Cite
|
Sign up to set email alerts
|

Optimising diffusion-weighted imaging in the abdomen and pelvis: comparison of image quality between monopolar and bipolar single-shot spin-echo echo-planar sequences

Abstract: Artefact reduction makes the bipolar DWI sequence preferable in abdominopelvic applications, although the trade-off in SNR may compromise ADC measurements in muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 21 publications
1
20
1
1
Order By: Relevance
“…In contrast with the results of earlier studies [16,17], we observed DWI using a monopolar acquisition to be the preferred technique, despite entailing shorter acquisition time. Specifically, this sequence exhibited higher eSNR in both volunteers and patents, as well as improved scores for subjective clarity of hepatic vessels, the posterior liver edge, and of the left lobe, and for overall diagnostic image quality, for at least one of two readers in both patients and volunteers.…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations
“…In contrast with the results of earlier studies [16,17], we observed DWI using a monopolar acquisition to be the preferred technique, despite entailing shorter acquisition time. Specifically, this sequence exhibited higher eSNR in both volunteers and patents, as well as improved scores for subjective clarity of hepatic vessels, the posterior liver edge, and of the left lobe, and for overall diagnostic image quality, for at least one of two readers in both patients and volunteers.…”
Section: Discussioncontrasting
confidence: 85%
“…Past authors have indicated that reducing artifacts from motion is ''paramount'' in this assessment and that the reduced distortions of the bipolar sequence counterbalance this approach's lower SNR [16]. Indeed, reduction of eddy currents by the bipolar sequence was regarded as having the ''key role'' in achieving higher image quality [16]. However, our experience at 3T was notably different, as we observed improved eSNR using the monopolar technique to be a dominant factor in influencing overall performance, possibly related to shorter liver T2 relaxation times at 3T [33].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Bu durum güçlü manyetik gradyanların hızlı bir şekilde değiştirilmesini ve bunun da öngörülemeyen üst üste manyetik alan gradiyentleri üreten girdap akıntılarına yol açma-sına neden olabilir [32,33]. Bunun sonucu DAG' da prostatın anatomik distorsiyonuna neden olmaktadır [34,35]. Bu bozulma, T2 ağırlıklı görüntülemeyle karşılaştırıldığında prostatın boyut, şekil ve konumundaki deği-şiklikler olarak ortaya çıkabilir.…”
Section: Difüzyon Ağırlıklı Görüntüleme İle İlgili Teknik Zorluklarunclassified